2016
DOI: 10.1073/pnas.1612441113
|View full text |Cite
|
Sign up to set email alerts
|

Stac3 has a direct role in skeletal muscle-type excitation–contraction coupling that is disrupted by a myopathy-causing mutation

Abstract: In skeletal muscle, conformational coupling between Ca V 1.1 in the plasma membrane and type 1 ryanodine receptor (RyR1) in the sarcoplasmic reticulum (SR) is thought to underlie both excitation-contraction (EC) coupling Ca 2+ release from the SR and retrograde coupling by which RyR1 increases the magnitude of the Ca 2+ current via Ca V 1.1. Recent work has shown that EC coupling fails in muscle from mice and fish null for the protein Stac3 (SH3 and cysteine-rich domain 3) but did not establish the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
86
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 29 publications
18
86
1
Order By: Relevance
“…One possibility is that Stac3 may be required for the proper conformation of DHPRs in T tubules required for voltage-dependent charge movement. Consistent with this, charge movement and voltage-gated Ca 2+ release are also reduced in myotubes from Stac3-null mice (26), although the magnitude of charge movement reduction in Stac3-null and Stac3 NAM -expressing zebrafish fibers was greater than that observed in mouse myotubes. In addition, the lack of proper folding of the DHPRα in the T-tubule membrane has been proposed as the basis for a similar near-complete absence of DHPR charge movement in the DHPRβ 1a -null zebrafish (17,24).…”
Section: Discussionsupporting
confidence: 67%
“…One possibility is that Stac3 may be required for the proper conformation of DHPRs in T tubules required for voltage-dependent charge movement. Consistent with this, charge movement and voltage-gated Ca 2+ release are also reduced in myotubes from Stac3-null mice (26), although the magnitude of charge movement reduction in Stac3-null and Stac3 NAM -expressing zebrafish fibers was greater than that observed in mouse myotubes. In addition, the lack of proper folding of the DHPRα in the T-tubule membrane has been proposed as the basis for a similar near-complete absence of DHPR charge movement in the DHPRβ 1a -null zebrafish (17,24).…”
Section: Discussionsupporting
confidence: 67%
“…Expression of STAC3 is restricted to skeletal muscle, where STAC3 associates with the voltage-gated calcium channel Ca V 1.1 and is involved in mediating voltage-induced calcium release from the sarcoplasmic reticulum (3,4). In nonmuscle cells, STAC3 was shown to facilitate functional membrane expression of Ca V 1.1 and alter the current properties of Ca V 1.2 (5), suggesting a role of STAC proteins as an L-type calcium channel (Ca V 1) regulator.…”
mentioning
confidence: 99%
“…We previously demonstrated that the stable association of STAC3 to the Ca V 1 channel complex in the triads of skeletal muscle relies on the C1 domain (7). In contrast, the NAM mutation, which impairs EC coupling and is located in the SH3-1 domain of STAC3 (2)(3)(4), did not abolish the interaction with the calcium channel (2,4,7). We therefore proposed that STAC3 establishes multiple interactions: one through the C1 domain, responsible for the stable anchoring of STAC3 to the channel, and another one through the SH3-1 domain, involved in EC coupling (7).…”
mentioning
confidence: 99%
“…This suggested that impaired Ca V 1.1 membrane trafficking might also cause the EC coupling deficiency in the STAC3 knockout models45. However, EC coupling was still impaired in muscle fibers of STAC3-null zebrafish embryos 48 hours post-fertilization, which contained normal levels of Ca V 1.15 and in STAC3 KO mouse myotubes, which contained substantial, but reduced, amount of Ca V 1.18. Thus, STAC3 appears to perform multiple functions in Ca V 1.1 trafficking and EC coupling.…”
mentioning
confidence: 99%